Ultra‐Flexible, Dielectric, and Thermostable Boron Nitride‐Graphene Fluoride Hybrid Films for Efficient Thermal Management. Issue 9 (9th March 2021) - Qiu, Wangkang; Lin, Weiguang; Tuersun, Yisimayili; Ou, Meilian; Chu, Sheng
Abstract: As an important 2D nanomaterial, boron nitride nanosheet (BNNS) has aroused much academic interest due to its high in‐plane thermal conductivity (TC) and good electrical insulation capability. However, the brittleness and low strength of high‐content BNNS films greatly limit its practical application. In the authors' work, densely layered films containing 2D exfoliated graphene fluoride sheets (GFS) and BNNS with similar phonon vibrational characteristics and intrinsic high TC, are fabricated via vacuum‐assisted filtration (VAF) using cellulose nanofiber (CNF) as the framework. The strong hydrogen bonding between the ternary components and tight "face‐to‐face" contact between the BNNS/GFS interfaces significantly improve the thermal pathway density. Superior in‐plane TC (55.65 W m −1 K −1 ) of the nanocomposite can be achieved at the 90 wt% BNNS‐GFS loading, a value of 114% greater than a BNNS/CNF counterpart. Additionally, the as‐prepared papery films show tolerance to bending, folding, humid environment, and high‐temperature flame. The newly developed hybrid films are promising for efficient thermal management applications in many electronic devices. Abstract : The authors present a filtration papermaking technique to produce flexible films filled with boron nitride and graphene fluoride. Good phonon spectrum matching and strong hydrogen bonding promote synergistic mechanisms and give rise to multifunctional properties, including ultrahigh thermal conductivity (55.65 W m −1 K −1 ), moderate tensile strength (30 MPa), ultralow dielectric constant and dielectric loss (2.18 and 8 × 10 –3 ), excellent thermal stability and hydrophobicity.